1983
DOI: 10.1107/s0108270183008483
|View full text |Cite
|
Sign up to set email alerts
|

Structures cristallines du [2.2.2]paracyclophane (I) (C24H24) et de son complexe avec le perchlorate d'argent (II) (C24H24.AgClO4)

Abstract: tures were refined to R values of 0.076 (I) and 0.062 (It) for 1245 and 1495 intensities respectively. In both cases, the conformations of the paracyclophane molecules are similar with respect to the orientation of the three aromatic rings around a threefold pseudo-axis of symmetry, the rings being parallel to that axis. In the complex, the Ag + ion lies on the threefold pseudo-axis, slightly off the cavity formed by the three rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 5 publications
6
33
0
Order By: Relevance
“…involving methylene bridges are similar to those found in previous studies (Cohen-Addad et al, 1983).…”
Section: C(14)supporting
confidence: 92%
“…involving methylene bridges are similar to those found in previous studies (Cohen-Addad et al, 1983).…”
Section: C(14)supporting
confidence: 92%
“…The optimized structure is consistent with the experimental C 3 structure (RMSD: 0.011 Å from a C 3 point group), where the silver center is located 1.383 Å above the center (exp. : 1.433 Å), in good agreement with the experimental data . The averaged Ag−C distance of 2.599 Å (exp.…”
Section: Resultsmentioning
confidence: 99%
“…In the original report the conformation of the complex [2.2.2]pCp–Ag I was speculated to have the Ag I cation at the center of the organic cavity. Further structural studies revealed that in such a π‐prismand complex, the silver cation is bonded to one face of the cavity involving a C=C double bond for each arene moiety, resulting in a η 2 :η 2 :η 2 coordination mode (or an overall η 6 ) because of symmetry and energetic considerations, as was recently described…”
Section: Introductionmentioning
confidence: 99%
“…The solid-state structures of 2a, 8 2b, 9 and 2c 6 have been reported, and extensive NMR studies have been carried out for the whole series 2. 4 The solid-state structure of the title compound 2a reveals that the benzene rings in this hydrocarbon are pla- …”
Section: Figurementioning
confidence: 99%